A study on prophagic and chromosomal sodC genes involvement in Escherichia coli O157:H7 biofilm formation and biofilm resistance to H2O2 - Raffaella Scotti; Laura Nicolini; Annarita Stringaro; Roberta Gabbianelli (Istituto Superiore di Sanità, 2015)
Introduction. Escherichia coli O157:H7 possesses one chromosomal and two prophagic sodC genes encoding for Cu,Zn superoxide dismutases. We evaluated the contribution of sodC genes in biofilm formation and its resistance to hydrogen peroxide. Methods. The biofilm of sodC deletion mutants has been studied, in presence or absence of hydrogen peroxide, by crystal violet in 96-well plates and Scanning Electron Microscopy on glass coverslips. Results. Deletion of prophagic sodC genes had no effect on biofilm construction, in contrast to the chromosomal gene deletion. Hydrogen peroxide treatment showed higher cell mortality and morphological alterations in sodC deletion mutants respect to wild type. These effects were related to the biofilm development stage. Conclusion. The role of the three SodCs is not redundant in biofilm formation and the resistance to oxidative damage. The stage of biofilm development is a crucial factor for an effective sanitization.